Strategic Planning for Student Guidance Information System Design in Tourism Department using Ward and Peppard Framework - Yerik Afrianto Singgalen (Universitas Bina Darma, 2023)
This study examines the challenges faced by students during the thesis completion process, including miscommunication, document loss, and difficulty scheduling guidance sessions. To address these issues, Ward and Peppard's method was utilized to design a strategic plan for the Tourism Department at Atma Jaya Catholic University of Indonesia. The research findings reveal that the implementation of the student guidance information system,